Pengembangan Desa Wisata Berbasis Kearifan Lokal: Menumbuhkan Jiwa Enterpneur Pelaku Usaha Melalui Appreciative Inquiry - Yuwono, Emmanuel Satyo; Wibowo, Doddy Hendro; Therik, Wilson MA (Universitas Kristen Satya Wacana Salatiga, 2024)
Banyubiru Village and Kemambang Village are located in Banyubiru Sub-district, Semarang Regency. Both villages have the potential for nature, arts, and village government management to become tourist villages. However, the management of the Tourism Village has not been optimized to drive the community's economy. The PkM activity aims to improve the entrepreneurial character of the Banyubiru Village Community who have entrepreneurs and managers of business units in the village. Solutions were offered through Focus Group Discussion (FGD) activities with Appreciative Inquiry and Psychoeducation approaches. There were 19 participants. The results of the activity showed that the participants were optimistic, happy, excited and interested in the training activities. Participants received direction to be able to realize their hopes and concrete steps to realize their entrepreneurial dreams and collaborate to build Banyubiru Tourism Village.